THE ROLE OF EXERCISES IN INCREASING VOCABULARY STUDENTS - Ismailova, Surmakhon (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
The article examines the special role of the mother tongue in school education, knowledge of the mother tongue, life as a means of educating students as a perfect person, teaching the mother tongue, teaching students the basics of the language, developing their speech, developing the ability to self-expression, as has been shown, is one of the most the pressing problems with which the student must acquire these important skills after graduation, regardless of their specialty.